Incorporation of SKI-G-801, a Novel AXL Inhibitor, With Anti-PD-1 Plus Chemotherapy Improves Anti-Tumor Activity and Survival by Enhancing T Cell Immunity - Lee, Wongeun; Kim, Dong Kwon; Synn, Chun-Bong; Lee, Hee Kyu; Park, Sungho; Jung, Dong-Sik; Choi, Yewon; Kim, Jae Hwan; Byeon, Youngseon; Kim, Young Seob; Lee, Seul; Lee, Soyeon; et al. (Frontiers in Oncology, 2022)
A recently developed treatment strategy for lung cancer that combines immune checkpoint inhibitors with chemotherapy has been applied as a standard treatment for lung adenocarcinoma (LUAD) and lung squamous cell carcinoma (LUSC), and it has improved the outcomes of chemotherapy. Maintenance treatment with anti-PD-1 antibody (aPD-1) enhances the effect of immunochemical combination therapy and improves therapeutic efficacy, which contributes toward a significant improvement in patient survival rates. The AXL receptor tyrosine kinase (AXL), which is expressed in tumor cells, plays an essential role in the resistance of cancers to chemotherapy and immunotherapy, and stimulates signaling associated with epithelial-mesenchymal transition (EMT) in metastatic cancer. AXL is thus an attractive target for controlling resistance to anti-tumor therapies. In this study, we examined the effect of AXL inhibitors on immune activation and tumor growth in TC1 and C3PQ mouse tumor models, in the context of clinical immunotherapy/chemotherapy and maintenance treatment, using an aPD-1 with/without pemetrexed. To determine the optimal timing for administration of SKI-G-801, an AXL inhibitor, we investigated its anti-tumor effects based on inclusion at the immunochemotherapy and maintenance therapy stages. We also performed flow cytometry-based immune profiling of myeloid cells and lymphoid cells at different points in the treatment schedule, to investigate the immune activation and anti-tumor effects of the AXL inhibitor. The addition of SKI-G-801 to the immune checkpoint inhibitor and chemotherapy stage, as well as the maintenance therapy stage, produced the best anti-tumor results, and significant tumor growth inhibition was observed in both the TC1 and C3PQ models. Both models also exhibited increased proportion of effector memory helper T cells and increased expression of CD86+ macrophages. Especially, regulatory T cells were significantly reduced in the TC1 tumor model and there was an increase in central memory cytotoxic T cell infiltration and an increased proportion of macrophages with high CD80 expression in the C3PQ tumor model. These results suggest increased infiltration of T cells, consistent with previous studies using AXL inhibitors. It is expected that the results from this study will serve as a stepping stone for clinical research to improve the existing standard of care.